User Experience Analysis with User Experience Questionnaire (UEQ) in Academic Information Systems: Analisis Pengalaman Pengguna dengan User Experience Questionnaire (UEQ) pada Sistem Informasi Akademik - Abdurahman Azis Lasawali; Agung Susilo Yuda Irawan; Rini Mayasari; Bagja Nugraha (SYSTEMATICS, 2022)
Technological growth in Indonesia is growing rapidly along with the times. The internet is one example of technological developments that can connect one user to another. One of the services that internet users often visit is a website. The website is one of the important means of disseminating and exchanging information. One of the things that must be considered in website development is the user experience. Therefore, in this study, we will discuss how to analyze the user experience or user experience of a website. The research method used in this study is the questionnaire method to obtain data and the User Experience Questionnaire (UEQ) method to analyze the data that has been collected. The case study in this research is the Academic System (SIAKAD) website of Universitas Singaperbangsa Karawang, assisted by tools, such as Microsoft Excel and UEQ to analyze the experience of users who use the website. Thus, it is hoped that the results of the analysis in this study can be used as evaluation material for future website development.